Common factors in serious case reviews of child maltreatment where there is a medical cause of death: qualitative thematic analysis - Peter Sidebotham; Julie Taylor; Joanna Garstang; Daisy Eatwell (BMJ Open)
Aim To identify the common factors in serious case reviews (SCRs) where a child has died of a medical cause.Design Qualitative thematic analysis.Background SCRs take place when neglect or abuse results in children dying or being seriously harmed. Known key factors within SCRs include parental substance misuse, mental health problems and domestic abuse. To date, there has been no investigation of children who die of a medical cause where there are concerns about child maltreatment.Data sources A list of SCRs relating to deaths through medical causes was provided from previous coded studies and accessed from the National Society for the Prevention of Cruelty to Children National Case Review Repository. Twenty-three SCRs with a medical cause of death from 1 April 2009 to 31 March 2017 were sourced.Results 20 children died of an acute condition and 12 of a chronic condition; 20 of the deaths were unexpected and maltreatment contributed to the deaths of 18 children. Most children were aged either <1 year or >16 years at the time of death. Many parents were caring for a child with additional vulnerabilities including behavioural issues (6/23), learning difficulties (6/23), mental health issues (5/23) or a chronic medical condition (12/23). Common parental experiences included domestic violence/abuse (13/23), drug/alcohol misuse (10/23), mental ill health or struggling to cope (7/23), criminal history (11/23) and caring for another vulnerable individual (8/23). Most children lived in a chaotic household characterised by missed medical appointments (18/23), poor school attendance (11/23), poor physical home environment (7/23) and disguised compliance (12/23). All 23 SCRs reported elements of abusive or neglectful parenting. In most, there was an evidence of cumulative harm, where multiple factors contributed to their premature death. At the time of death, 11 children were receiving social care support.Conclusion Although the underlying medical cause of the child’s death was often incurable, the maltreatment that often exacerbated the medical issue could have been prevented.